(untitled) (Linguist, 2025)
In this study; I will re-examine the debate having taken place in the ancient Arab linguistic thought as well as in the modern linguistic theories about the Form vs Content dichotomy and its impact on the architecture of linguistic models.My main aim will be to show that the subject matter of such a debate could be conceived of as a mere difference in the viewpoint from which the communication process is intended to be approached.